2010
DOI: 10.2169/internalmedicine.49.3573
|View full text |Cite
|
Sign up to set email alerts
|

Development of Graves' Hyperthyroidism Caused an Adrenal Crisis in a Patient with Previously Unrecognized Non-classical 21-hydroxylase Deficiency

Abstract: A 75-year-old woman was found to be unconscious in hospital. She was febrile with a temperature of 38.4 . She had hypotension (blood pressure 80/40 mmHg) with serum Na 132 mEq/L and K 5.7 mEq/L (serum Na/K = 23.2), and serum cortisol 0.91 μg/dL, indicative of adrenal failure. She was admitted for the treatment of Graves' hyperthyroidism, and was found to be unconscious in hospital. We encountered a patient with unrecognized adrenocortical disease, in whom development of Graves' hyperthyroidism caused an adrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…One can easily appreciate that the same intervention with the same percentage elevation of 17-OHP in a female patient with amenorrhea, acne, hirsutism, alopecia, or infertility might have been very clinically useful in addressing these issues. Furthermore, NCAH patients under extreme stress may experience adrenal crisis [12], possibly justifying its treatment even in asymptomatic patients.…”
Section: Resultsmentioning
confidence: 99%
“…One can easily appreciate that the same intervention with the same percentage elevation of 17-OHP in a female patient with amenorrhea, acne, hirsutism, alopecia, or infertility might have been very clinically useful in addressing these issues. Furthermore, NCAH patients under extreme stress may experience adrenal crisis [12], possibly justifying its treatment even in asymptomatic patients.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in the present case, the symptoms of occult nonclassic 11β OHD, including hypertension and hypokalemia, seem to have aggravated the symptoms of TPP. Takasu et al reported a case of Grave's disease caused an adrenal crisis in a patient with previously unrecognized nonclassic 21 hydroxylase deficiency (10). Increased levels of thyroid hormone may play an etiologic role in the development and aggravation of symptoms if unrecognized nonclassic congenital adrenal hyperplasia is present.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that elevated thyroid hormone levels in the setting of Graves’ disease can unmask previously undiagnosed NCAH 24 25. Elevated thyroid hormone can increase the turnover of cortisol and consequently an occult NCAH may become symptomatic, or even lead to adrenal crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated thyroid hormone can increase the turnover of cortisol and consequently an occult NCAH may become symptomatic, or even lead to adrenal crisis. Takasu et al 24 have reported Graves’ disease causing adrenal crisis in a 75-year-old patient with previously unrecognised non-classical 21-hydroxylase deficiency. Also Kim et al 25 reported a case of thyrotoxic periodic paralysis with Graves’ disease leading to a late diagnosis of non-classic 11β-hydroxylase deficiency.…”
Section: Discussionmentioning
confidence: 99%